Convective boundary layer flow of brinkman-viscoelastic fluid over a bluff body - Siti Farah Haryatie, Mohd Kanafiah (2023)
The exploration of heat transference in relation to fluid flow problems is important, especially for non-Newtonian fluids. The use of a particular fluid can be found in many industrial applications such as oil and gas industries, automotive, and manufacturing processes. Therefore, this thesis presents numerical solutions and studies the characteristics of a fluid of five problems that combines the properties of viscosity and elasticity together with porosity conditions called the Brinkman-viscoelastic model. The flow is assumed to move over a bluff body such as a horizontal circular cylinder and sphere under consideration of the constant wall temperature (CWT) and convective boundary condition (CBC). The five considered problems include the (1) boundary layer flow of Brinkman-viscoelastic fluid passing through a horizontal circular cylinder, (2) free convection of Brinkman-viscoelastic fluid passing through a horizontal circular cylinder, (3) mixed convection of Brinkman-viscoelastic fluid passing through a horizontal circular cylinder, (4) free convection of Brinkman-viscoelastic fluid passing through a sphere, and (5) mixed convection of Brinkman-viscoelastic fluid passing through a sphere. The mathematical model was transformed to a less complex form by utilising non-dimensional variables and non-similarity transformation. The resulting equations are in the partial differential equation form. Subsequently, the equations were solved by employing the Keller-box method and the numerical algorithm was developed in the MATLAB tool. To validate the model for all problems, numerical values from current and earlier reports were compared in a particular case. The solutions were conveniently evaluated by observing the plotted graphs in order to capture the propensity of the fluid’s behaviour in response to the adjusting parameters. The studied parameters such as viscoelastic, Brinkman, mixed convection, and the Biot number were analysed to obtain the velocity and temperature profiles together with the skin friction coefficient and Nusselt number. The results for all problems showed that when the viscoelastic and Brinkman parameters increased, the velocity dropped and the temperature increased for CWT and CBC cases, while the mixed convection parameter reacted in an opposite trend. However, the CWT case contributed to higher velocity than the CBC case. Additionally, an increase in the Biot number increased the velocity and temperature. Of all the parameters considered in this study, the viscoelastic parameter could hold the boundary layer separation for both CWT and CBC. Meanwhile, the mixed convection parameter increased the skin friction and heat transfer rate for the CWT case, as followed by the Biot number in the CBC case. These numerical results can be used to assist engineers in making heat transfer process decisions and accurately verifying experimental investigations.